Comparative analysis of extracellular vesicle isolation methods from human AML bone marrow cells and AML cell lines - Lang, Jonas B.; Buck, Michèle C.; Rivière, Jennifer; Stambouli, Oumaima; Sachenbacher, Ken; Choudhary, Purva; Dietz, Hendrik; Giebel, Bernd; Bassermann, Florian; Oostendorp, Robert A. J.; Götze, Katharina S.; Hecker, Judith S. (Frontiers in Oncology, 2022)
Cellular crosstalk between hematopoietic stem/progenitor cells and the bone marrow (BM) niche is vital for the development and maintenance of myeloid malignancies. These compartments can communicate via bidirectional transfer of extracellular vesicles (EVs). EV trafficking in acute myeloid leukemia (AML) plays a crucial role in shaping the BM microenvironment into a leukemia-permissive niche. Although several EV isolation methods have been developed, it remains a major challenge to define the most accurate and reliable procedure. Here, we tested efficacy and functional assay compatibility of four different EV isolation methods in leukemia-derived EVs: 1. membrane affinity-based: exoEasy Kit alone and 2. in combination with Amicon filtration; 3. precipitation: ExoQuick-TC; and 4. ultracentrifugation (UC). WB analysis of EV fractions showed the highest enrichment of EV marker expression (e.g., CD63, HSP70, TSG101) by precipitation with removal of overabundant soluble proteins (e.g., BSA) which were not discarded using UC. Besides presence of damaged EVs after UC, intact EVs were successfully isolated with all methods as evidenced by highly maintained spherical and cup shaped vesicles in transmission electron microscopy. Nanoparticle tracking analysis of EV particle size and concentration revealed significant differences in EV isolation efficacy, with exoEasy Kit providing the highest EV yield recovery. Of note, functional assays with exoEasy Kit-isolated EVs showed significant toxicity towards treated target cells (e.g., mesenchymal stromal cells (MSC)), which was abrogated when combining exoEasy Kit with Amicon filtration. Additionally, MSC treated with GFP-tagged exoEasy Kit-isolated EVs did not show any EV uptake, while EV isolation by precipitation demonstrated efficient EV internalization. Taken together, the choice of EV isolation procedure significantly impacts yield and potential functionality of leukemia-derived EVs. The cheapest method (UC) resulted in contaminated and destructed EV fractions while the isolation method with the highest EV yield (exoEasy Kit) appeared incompatible with functional assays. We identified two methods (precipitation-based ExoQuick-TC and membrane affinity-based exoEasy Kit combined with Amicon filtration) yielding pure and intact EVs, also suitable for application in functional assays. This study highlights the importance of selecting the right EV isolation method depending on the desired experimental design.